Determination of the features of the use of three-component vegetable and fruit paste in marmalade technology - Samokhvalova, Olga; Cherevko, Oleksander; Dmytrevskyi, Dmytro; Budnyk, Nina; Fomina, Iryna; Gurskyi, Petro; Sova, Nataliia; Koshulko, Vitalii; Tesliuk, Yuliia; Kolianovska, Liudmyla (Eastern-European Journal of Enterprise Technologies, 2024)
The object of the study is the technology of marmalade based on pumpkin, apple and dogwood paste. The development of a vegetable and fruit paste allows to solve the issue of marmalade structure formation, provide high organoleptic quality indicators, without the use of dyes and essences, enrich the chemical composition of products and give functional properties. Due to the use of short-term low-temperature concentration and a well-founded recipe (pumpkin 50 %, apple 35 %, dogwood 15 %). The paste contains a significant amount of functional ingredients, which is confirmed by the study of its chemical composition. The paste has a dynamic viscosity of 280 Pa∙s, a high content of non-starch polysaccharides of 3.89±0.11 g, vitamin C of 1.89±0.05 mg, β-carotene 21.13±0.60. For optimal management of the concentration process (55…65 °C), an effective viscosity is set in the range of 5…35 Paּ∙s. The improved method of producing marmalade based on pumpkin, apple and dogwood paste is characterized by increased quality. The marmalade mass at a temperature of 80…82 °C before gelatinization has a viscosity 24 % higher than the control. The developed marmalade has a pleasant ruby color and a lingering consistency. The content of non-starch polysaccharides, mainly pectin substances and vitamin C increases almost twice. The new marmalade is characterized by the presence of vitamins A, C, E and β-carotene. The number of macro- and microelements increases significantly compared to the control sample. According to the content of non-starch polysaccharides, vitamin A, β-carotene and potassium, marmalade based on vegetable and fruit paste can be classified as functional, since the percentage of provision of these substances per day exceeds 10 %. The method of marmalade production can be implemented at confectionery enterprises